Difference between revisions of "009A Sample Final A, Problem 2"
Jump to navigation
Jump to search
m |
m |
||
Line 13: | Line 13: | ||
|These are problems involving some more advanced rules of differentiation. In particular, they use | |These are problems involving some more advanced rules of differentiation. In particular, they use | ||
|- | |- | ||
− | |'''The Chain Rule:''' If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: - | + | |'''The Chain Rule:''' If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: -15%;">g</math> are differentiable functions, then |
|- | |- | ||
|<br> <math>(f\circ g)'(x) = f'(g(x))\cdot g'(x).</math> | |<br> <math>(f\circ g)'(x) = f'(g(x))\cdot g'(x).</math> | ||
|- | |- | ||
− | |<br>'''The Product Rule:''' If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: - | + | |<br>'''The Product Rule:''' If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: -15%;">g</math> are differentiable functions, then |
|- | |- | ||
|<br> <math>(fg)'(x) = f'(x)\cdot g(x)+f(x)\cdot g'(x).</math> | |<br> <math>(fg)'(x) = f'(x)\cdot g(x)+f(x)\cdot g'(x).</math> | ||
|- | |- | ||
− | |<br>'''The Quotient Rule:''' If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: - | + | |<br>'''The Quotient Rule:''' If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: -15%;">g</math> are differentiable functions and <math style="vertical-align: -25%;">g(x) \neq 0</math>, then |
|- | |- | ||
|<br> <math>\left(\frac{f}{g}\right)'(x) = \frac{f'(x)\cdot g(x)-f(x)\cdot g'(x)}{\left(g(x)\right)^2}. </math> | |<br> <math>\left(\frac{f}{g}\right)'(x) = \frac{f'(x)\cdot g(x)-f(x)\cdot g'(x)}{\left(g(x)\right)^2}. </math> |
Revision as of 21:35, 26 March 2015
2. Find the derivatives of the following functions:
(a)
(b)
(c)
Foundations: |
---|
These are problems involving some more advanced rules of differentiation. In particular, they use |
The Chain Rule: If and are differentiable functions, then |
The Product Rule: If and are differentiable functions, then |
The Quotient Rule: If and are differentiable functions and , then |
Solution:
Part (a): |
---|
We need to use the quotient rule: |
Part (b): |
---|
Both parts (b) and (c) attempt to confuse you by including the familiar constants and . Remember - they are just constants, like 10 or 1/2. With that in mind, we really just need to apply the chain rule to find |
Part (c): |
---|
We can choose to expand the second term, finding |
We then only require the product rule on the first term, so |